Food and water security under global change: CPWF policy brief - Ringler, Claudia (CGIAR Challenge Program on Water and Food, 2009)
Over the coming decades, global change will have an impact on food and water security in highly significant and yet uncertain ways. There are strong indications that developing countries will bear the brunt of any adverse conditions, particularly those steeming from climate change. T his is largely because poverty levels are high, and developing-country capacity to adapt to global change is weak. Furthermore, the rural populations of developing countries—for whom agricultural production is the primary source of direct and indirect employment and income—will be most affected due agriculture’s vulnerability to global change processes. T he agricultural sector is the largest consumer of water resources, and variability in water supply has a major influence on health and welfare in poor areas. With water scarcity and extreme weather events expected to increase under climate change, water security could decline significantly in rural areas and in agriculture. Consequently, it is important to understand the impacts of global change (in terms of climate, demography, technology, and so on), on agriculture and natural resources in developing countries and to develop adaptive capacity to respond to these impacts. Moreover, there is a need to develop informed and effective adaptation measures and investment options that can be taken now to alleviate adverse impacts of global change in the future.